Pathology and Function of Conduction Tissue in Fabry Disease Cardiomyopathy. (August 2015) - Frustaci, Andrea; Morgante, Emanuela; Russo, Matteo A.; Scopelliti, Fernanda; Grande, Claudia; Verardo, Romina; Franciosa, Pasquale; Chimenti, Cristina
<x xml:space="preserve">Abstract</x> Background— Cardiac arrhythmias are common in Fabry disease (FD) and may occur in prehypertrophic cardiomyopathy suggesting an early compromise of conduction tissue (CT). Therefore, FD X-linked and CT may be variously involved in male and female patients with FD cardiomyopathy, affecting CT function. Methods and Results— Among 74 patients with endomyocardial biopsy diagnosis of FD cardiomyopathy, 13 (6 men; 7 women; mean age, 50.1±13.5 years; maximal wall thickness, 16.7±3.7 mm) had CT included in histological specimens and 6 also at electron microscopy. CT glycolipid infiltration was defined as focal, moderate, extensive, or massive, if involved ⩽30%, ⩽50%, >50%, or 100% of cells; identified as loosely arranged small myocytes positive to HCN4 immunostaining, supplied by a centrally placed thick-walled arteriole. CT involvement was correlated with age, sex, and α-Gal gene mutation. CT function was evaluated by electrophysiological study and arrhythmias at Holter registration. CT infiltration was focal/moderate in 4 women with no arrhythmias and normal electrophysiological study, extensive in 3 women with atrial or ventricular arrhythmias and short HV interval, and massive in 6 men with atrial fibrillation or ventricular arrhythmias and short HV. Short PR/AH with increased refractoriness was additionally found in 3 patients with extensive/massive CT infiltration. A male patient with the shortest HV presented infra-Hissian block during decremental atrial stimulation. There was no correlation with age, maximal wall thickness, and type of gene mutation. Conclusions— CT infiltration in FD cardiomyopathy is constant in men and variable in women because of skewed X-chromosome inactivation; its extensive/massive involvement causes accelerated conduction with prolonged refractoriness and electric instability.